The effect of service climate,service bahavior,and service quality on customer satisfaction in Muslim-friendly hotels - Noor Amalina Mat Yusof (International Institute for Halal Research and Training, International Islamic University Malaysia, 2021)
Customers’ satisfaction is a critical component in providing a competitive advantage for Islamic tourism and consequently, sustain the industry. This study highlights Muslim-friendly hotels (MFHs) which are considered one of the most important elements in the Islamic tourism industry. This study aims to examine effect of service climate, service behavior and service quality on customer satisfaction in Muslim-friendly hotels. This study has seven main objectives: (1) to examine the relationship between service climate and customer satisfaction in Muslim-friendly hotels, (2) to examine the relationship between service climate and service behavior in Muslim-friendly hotels, (3) to examine the relationship between service behavior and customer satisfaction in Muslim-friendly hotels, (4) to examine the mediation effect of service behavior on the relationship between service climate and customer satisfaction in Muslim-friendly hotels, (5) to examine the relationship between service climate and service quality in Muslim-friendly hotels, (6) to examine the relationship between service quality and customer satisfaction in Muslim-friendly hotels, and (7) to examine the mediation effect of service quality on the relationship between service climate and customer satisfaction in Muslim-friendly hotels. Particularly, contemplate social interaction which occurs between employees and customers. The social exchange theory (SET) and an extended SERVPERF model guided this study, and a 55-item instrument was adopted. As this study involves the employee-customer relationship, two sets of instruments were developed: (1) information about the service climate and employees’ service behavior were obtained from employees who are involved with service delivery at the MFHs, while (2) information about service quality and customer satisfaction were evaluated by customers. Based on 120 employees working at MFHs and 120 customers who visited at MFHs at least once, usable data was gathered at 24 MFHs, and the data were analyzed using structural equation modeling (SEM) by using the R version 3.1.6 software. It was found that the service climate significantly influenced employees’ behavior and service quality. In addition, service quality mediated the relationship between service climate and customers’ satisfaction. These empirical findings clearly evinced the relationship between employees and customers in relation to customers’ satisfaction. This findings from this study offer better understanding of social interaction within Malaysian MFHs in the pursuit of customers’ satisfaction. Furthermore, this study proposed a new strategy in managing employees to provide excellent services in the context of MFHs in Malaysia.